2020
DOI: 10.1259/bjr.20191028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of deep learning-based vascular extraction and stenosis detection technique for coronary artery disease

Abstract: Objective: To investigate the diagnostic performance of deep learning (DL)-based vascular extraction and stenosis detection technology in assessing coronary artery disease (CAD). Methods: The diagnostic performance of DL technology was evaluated by retrospective analysis of coronary computed tomography angiography in 124 suspected CAD patients, using invasive coronary angiography as reference standard. Lumen diameter stenosis ≥50% was considered obstructive, and the diagnostic performances were evaluated at pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…The training set, validation set and test set were used for training model, tuning model and evaluating model performance respectively. This diagnostic performance of this system has been validated and reported in a recent published work 37 .…”
Section: Methodsmentioning
confidence: 69%
“…The training set, validation set and test set were used for training model, tuning model and evaluating model performance respectively. This diagnostic performance of this system has been validated and reported in a recent published work 37 .…”
Section: Methodsmentioning
confidence: 69%
“…Remarkable progress have been made in applying different machine learning algorithms with medical features for detecting different diseases such as various types of cancer and cardiovascular diseases [12][13][14][25][26][27]. Abdar et al proposed a nested ensemble nu-support vector classification (NE-nu-SVC) model for the diagnosis of CAD [26].…”
Section: Discussionmentioning
confidence: 99%
“…The features selection is the first step and plays a crucial role in machine learning, which can impact the detection accuracy of the machine learning classifier [12]. Studies suggested that many features were clinically associated with CAD and varied with the degrees of diseases, including physiological-based features such as blood pressure, blood glucose, blood lipids, age, obesity degree, and overweight [1], signal-based features such as electrocardiogram (ECG) and phonocardiogram (PCG) signals [13], computer imaging-based features such as "gray value" [14], and morphological features such as diameter stenosis [15]. Although all these features were potentially used in machine learning for the detection of CAD, the performance of the machine learning classifier depended on the quality of features used.…”
Section: Introductionmentioning
confidence: 99%
“…The patients in the test set were under ICA examination with an interval of less than 30 days after CCTA procedure. We have previously reported the validation of our deep learning system [13,14]. Before training, the aorta, coronary artery and plaques were labeled on each image by a multi-layer manually annotation system consisting of multiple layers of trained graders.…”
Section: Deep Learningmentioning
confidence: 99%